The main issues in restructuring the rules regulating the financial derivatives market - a theoretical analytical approach - صبيحة قاسم هاشم,; هنادي صكرمكطوف, (Iraqi Journal for Administrative Sciences, 2025)
The trading in the over-the-counter(OTC) market is regulated have contributed in the ambiguity of derivatives markets, and worked to limit competition, and which is reflected in the increased margin enjoyed by the traders, and increase prices, which should end users (industrial companies and non-financial) pay it. This will reflect also the negative damage borne by the real economy of the country. To solve this problem had to be reconsidered in the core issues to reshape the rules governing the derivatives market, and work on the transfer of trade financial derivatives to market more organized, working requirements side daily to ensure overall stability, and work transparency to pay competition, and the reduction of the margin, and increasing the depth of the market. Add to the clearinghouse of a prominent role in remove the credit risk inherent in bilateral OTC contracts by guaranteeing payment on both sidesof derivatives contracts. Efforts to implement the antitrust laws could be seen as complementary to the binding regulations for derivatives, and to overcome the forces of the enormous pressure of investment banks, which helps to ensure global financial stability